Narasi Bias Gender Dalam Tafsir Nusantara - Mamluatun Nafisah (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2023)
This paper departs from the interpretation of couples in heaven who are considered less friendly to women's groups. This paper discusses how the Nusantara interpreters interpret zauj as a partner in heaven. There are five books of interpretation chosen in this paper, namely Tafsir Marah Labid, Tafsir Al-Ibriz, Tafsir an-Nur, Tafsir Al-Azhar, and Tafsir Al-Misbah. To find out their views on the meaning of zauj as a partner in heaven, the author uses a historical approach. The results of this study conclude that the interpretation of Quraish Shihab in Tafsir Al-Misbah on the word zauj as a partner in heaven is much more gender-friendly than the previous commentators. If mapped, Nawawi al-Bantani, Bisri Musthofa, Hamka and Hasbi tend to follow the current view of the traditional commentators.